1978
DOI: 10.1121/1.381984
|View full text |Cite
|
Sign up to set email alerts
|

Presumed noise-induced permanent threshold shift resulting from exposure to an A-weighted Leq of 89 dB

Abstract: The noise-induced permanent threshold shift (NIPTS) resultings form up to ten years of exposure to an average A-weighted sound level Leq of 89 dB was investigated. Prior occupational noise exposure was controlled for by eliminating subjects with previous high-noise-level jobs or uncertain exposure histories. The final population consisted of 42 males and 58 females working a steady-state broadband noise environments. No attempt was made to screen subjects for any auditory pathology. A 222-subject control group… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
11
0
3

Year Published

1982
1982
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 0 publications
3
11
0
3
Order By: Relevance
“…So sociacusis remains, in my opinion, still the prime suspect in this mystery, although an inherent difference in susceptibility is of course possible. This comment applies as well to the results reported by Berger et al (1978), who showed that women working in 89-dBA textile noise for 10 years accumulate less than 5 dB of inferred NIPTS at 4 kHz, while men working in the same environment end up with nearly 20 dB, as Passchier-Vermeer's growth curves predict.…”
Section: Animal Exposures: Total and Equal Energysupporting
confidence: 56%
“…So sociacusis remains, in my opinion, still the prime suspect in this mystery, although an inherent difference in susceptibility is of course possible. This comment applies as well to the results reported by Berger et al (1978), who showed that women working in 89-dBA textile noise for 10 years accumulate less than 5 dB of inferred NIPTS at 4 kHz, while men working in the same environment end up with nearly 20 dB, as Passchier-Vermeer's growth curves predict.…”
Section: Animal Exposures: Total and Equal Energysupporting
confidence: 56%
“…Similarmente, la posibilidad de presentar escotoma en la frecuencia 6 kHz del mismo oído es 2,3 veces mayor en el caso de los expuestos a ruido dental que en los no expuestos; siendo esto estadísticamente significativo. Todos los valores reportados son ajustados de acuerdo al sexo del estudiante debido a que hubo una diferencia en la proporción entre los grupos, y a la importancia teórica de esa covariable [17][18][19][20] (Tabla 5). Finalmente, en cuanto a las mediciones obtenidas con sonómetro se obtuvo que la frecuencia con mayor nivel emitida por el rotomotor correspondió a 4 kHz (mediana de 68,1 dB, con un mínimo de 67,5 y un máximo de 69,4 dB).…”
Section: Resultsunclassified
“…Tanto Berger y col 17 quienes estudiaron trabajadores en industrias, como Niskar y col 18 los que consideraron sujetos entre 6 y 19 años, observaron una menor frecuencia de pérdida producto del ruido en el sexo femenino. Además, se cree que podría existir una exposición diferencial según sexo a actividades ruidosas 19,20 .…”
Section: Introductionunclassified
“…The mechanism of progressive pathological changes and damage to the cochlea caused by aging are also often the same factors indicated to increase a person's susceptibility to NIHL (Pyykkö, et al, 2007;Dobie, 2008). Some studies have shown that the effect of noise on hearing is most in the early years of exposure but in later years the age related hearing loss contributes more to the total loss of hearing than NIHL (Berger, Royster & Thomas, 1978;Dobie, 2008;Pyykkö, et al, 2007). In a study by Dobie (2008) predictions were made about the burden of NIHL and ARHL in the United States (US).…”
Section: Introductionmentioning
confidence: 99%